2014
DOI: 10.1002/2013jg002515
|View full text |Cite
|
Sign up to set email alerts
|

Mapping forest stand age in China using remotely sensed forest height and observation data

Abstract: Forest stand age plays a crucial role in determining the terrestrial carbon source or sink strength and reflects major disturbance information. Forests in China have changed drastically in recent decades, but quantification of spatially explicit forest age at national level has been lacking to date. This study generated a national map of forest age at 1 km spatial resolution using the remotely sensed forest height and forest type data in 2005, as well as relationships between age and height retrieved from fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 84 publications
3
85
0
Order By: Relevance
“…Regarding the pattern of these key processes, f auto first decreased and then increased as temperature increased at the turning point of approximately 11°C, which was highly congruent with the synthetic analysis based on the global forest database and could be ascribed to the asymmetric response of RE and GPP to rising temperature (Piao et al., ). The decrease in f woo with increasing latitude and decreasing temperature was supported by the inventory‐based synthesis in Chinese forests (Li, Zhou, & He, ), and this pattern may be explained by the adaptive strategies of forest trees to temperature (Reich et al., ) as well as the age‐structure‐related strategy (Zhou, Shi, et al., ), which tends to allocate less C to the structural pool in old forests mainly distributed in cold, high‐latitude regions in China (Zhang et al., ). θ woo and θ som both increased with rising temperature, which agrees well with the variation in the plant mortality rate based on forest inventory (Mantgem et al., ; Zhou, Peng, et al., ) and the variation in soil C decomposition based on Rs observations from the chamber or isotope method (Chen, Huang, Zou, & Shi, ; Frank, Pontes, & McFarlane, ; Karhu et al., ).…”
Section: Discussionmentioning
confidence: 87%
“…Regarding the pattern of these key processes, f auto first decreased and then increased as temperature increased at the turning point of approximately 11°C, which was highly congruent with the synthetic analysis based on the global forest database and could be ascribed to the asymmetric response of RE and GPP to rising temperature (Piao et al., ). The decrease in f woo with increasing latitude and decreasing temperature was supported by the inventory‐based synthesis in Chinese forests (Li, Zhou, & He, ), and this pattern may be explained by the adaptive strategies of forest trees to temperature (Reich et al., ) as well as the age‐structure‐related strategy (Zhou, Shi, et al., ), which tends to allocate less C to the structural pool in old forests mainly distributed in cold, high‐latitude regions in China (Zhang et al., ). θ woo and θ som both increased with rising temperature, which agrees well with the variation in the plant mortality rate based on forest inventory (Mantgem et al., ; Zhou, Peng, et al., ) and the variation in soil C decomposition based on Rs observations from the chamber or isotope method (Chen, Huang, Zou, & Shi, ; Frank, Pontes, & McFarlane, ; Karhu et al., ).…”
Section: Discussionmentioning
confidence: 87%
“…Repeated historical human disturbances and recent national afforestation campaigns are the main reasons for China's relatively young forests. Similar to a previous study [ Zhang et al , ], the young forests are mainly found in south China and peripheral regions of large mountains in northeast China (Figure a), in accordance with regions of heavy national afforestation campaigns since the end of 1970s. Recent statistics [ State Forestry Administration of the People's Republic of China's , ] suggest that 42% of the total planted forests are distributed in six southern provinces (Guangxi, Guangdong, Hunan, Sichuan, Yunnan, and Fujian).…”
Section: Resultsmentioning
confidence: 99%
“…The large variation of the optimized parameters indicates large distinctions of age-height relationships among different forest types, even for some types whose dominant species belong to the same genus (e.g., Pinus tabulaeformis and Pinus massoniana), which indicates that it could be a large source of uncertainties to assume similar growth parameters for closely related species or forest types [e.g., Yin et al, 2015;Zhang et al, 2014]. Furthermore, our results also highlight the significant influence of environment factors on ageheight relationship, which was usually ignored in previous tree growth equations [Wang et al, 2007;Dai et al, 2011;Zhang et al, 2014].…”
Section: Parameters In Height-age Equationmentioning
confidence: 99%
“…This dataset was downloaded from http://landscape.jpl.nasa.gov. It provided estimated canopy height values across the land surface, and had good correlation with the tree height observed in the field at both global and regional scales (Simard et al 2011, Zhang et al 2014.…”
Section: Remote Sensing Data (Ndvi and Canopy Heights)mentioning
confidence: 92%